Brand Rejuvenation and Consumer Behavior (International Journal of Food and Nutritional Sciences, 2021)
This research investigates the impact of brand rejuvenation strategies on consumer behavior and brand perception. Utilizing a quantitative approach, data were collected from a diverse sample population in Pune City through structured questionnaires and analyzed using statistical methods. The findings reveal a substantial positive influence of brand rejuvenation on consumer purchasing decisions, with respondents expressing increased inclination and a noticeable shift in tendencies post-rejuvenation. Moreover, the study underscores the strategic importance of brand rejuvenation in shaping positive perceptions of brand image, appeal, relevance, modernity, quality, and value. These insights hold implications for marketers and brand strategists, emphasizing the need for thoughtful rejuvenation initiatives to enhance consumer engagement and foster a contemporary brand identity. Future research could delve into the long-term effects, specific components of rejuvenation, industry variations, and the influence of digital platforms on brand rejuvenation effectiveness